2015
DOI: 10.14445/22315373/ijmtt-v28p504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Jigsaw IV Cooperative Learning Strategy (J4CLS) on Academic Performance of Secondary School Students in Geometry

Abstract: This study is an attempt to solve the persistent poor performance of students in geometry in senior secondary schools in Kaduna State, Nigeria. The study was guided by two research questions and two hypotheses. The quasi experimental research design involving a pretest and posttest was used. The population of the study comprised of 4624 senior secondary school year two (SS2) students of the public secondary schools in Zaria Educational Zone. Two coeducation schools were selected by the simple random sampling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
3
12
0
1
Order By: Relevance
“…The results of the analyses related to the hypothesis two indicated no significant difference in the performance of male and female students taught Organic Chemistry using Jigsaw IV cooperative learning strategy. This finding is in line with that of Adeyemi (2008); Ajaja and Eravwoke (2010); Yusuf, etal (2015); Timayi et al (2015) who individually found out that there is no gender difference in the academic performance of male and secondary school students exposed to Jigsaw IV Cooperative Learning Strategy. The finding is however in disagreement with that of Olson (2002) which reported that females performed better than males students when taught mathematics using Jigsaw II cooperative learning.…”
Section: Discussion Of Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the analyses related to the hypothesis two indicated no significant difference in the performance of male and female students taught Organic Chemistry using Jigsaw IV cooperative learning strategy. This finding is in line with that of Adeyemi (2008); Ajaja and Eravwoke (2010); Yusuf, etal (2015); Timayi et al (2015) who individually found out that there is no gender difference in the academic performance of male and secondary school students exposed to Jigsaw IV Cooperative Learning Strategy. The finding is however in disagreement with that of Olson (2002) which reported that females performed better than males students when taught mathematics using Jigsaw II cooperative learning.…”
Section: Discussion Of Resultssupporting
confidence: 90%
“…Becker in Lakpini (2006) opined teachers spoke more frequently to boys, asked the boys more questions, praised boys for quality work and girls for neatness. Even though, Ajaja and Eravwoke (2010) and Timayi et al (2015), reported that gender had no effect on academic achievement of students in cooperative learning. These contradictory findings have caused for inclusion of gender as one of the moderating variable for this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooperative learning has an important goal, namely to provide knowledge, concepts, abilities, and necessary understanding (Slavin, 2005: 33). As one of cooperative learning, the Jigsaw method (Suratno, 2005) provides six versions of cooperative learning methods, including Jigsaw I, Jigsaw II, Jigsaw III, Jigsaw IV, Reverse Jigsaw, and Jigsaw Subjects that can be used by teachers for classroom learning (Timayi, et al, 2015). The learning model used in this study is the Jigsaw IV and Reverse Jigsaw methods.…”
Section: Introductionmentioning
confidence: 99%
“…Journal homepage: https://jurnal.uns.ac.id/joive/index material (Timayi, et al, 2015). Meanwhile, Heeden (Samuel, 2018) concluded that the difference between Reverse Jigsaw and Jigsaw was in the Reverse Jigsaw technique which arranges students of expert groups to teach the entire class rather than returns them to their original groups to teach content.…”
Section: Introductionmentioning
confidence: 99%